2009
DOI: 10.15218/zjms.2009.019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of T-helper 1 Cytokines (IFN-y and TL-2) in HBV Infected patients and Individuals vaccinated with Recombinant HB Vaccine

Abstract: Background and objective: The specific cellular immune responses play a main role in the hepatic necrosis that occurs with hepatitis B virus (HBV) infection. Interferon-g (IFN-g) and interleukin-2 (IL-2) are considered examples on T helper 1(Th1) cytokines which required for host antiviral immune response and involved in cell-mediate immunity against HBV infection. This study was designed to estimation T-helper 1 cytokines (IFN-g and IL-2) in HBV infected patients and individuals vaccinated with recombinant HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Therefore, circulating GM-CSF levels may correlate with the degree of liver fibrosis and systemic inflammation in CLD of different etiologies including HCV infection and NASH. Moreover, our findings are in agreement with Al-Barzinji and Ahmed [29] who demonstrated significant increase in GM-CSF levels in patients in the acute phase of hepatitis compared to those with chronic hepatitis and control subjects. Our findings also revealed a progressive increase in GM-CSF levels which match the severity of the disease and the stage of liver fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, circulating GM-CSF levels may correlate with the degree of liver fibrosis and systemic inflammation in CLD of different etiologies including HCV infection and NASH. Moreover, our findings are in agreement with Al-Barzinji and Ahmed [29] who demonstrated significant increase in GM-CSF levels in patients in the acute phase of hepatitis compared to those with chronic hepatitis and control subjects. Our findings also revealed a progressive increase in GM-CSF levels which match the severity of the disease and the stage of liver fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Muller et al (1994) exhibited that mice IFNAR lacking are more vulnerable to viral infections , such as vesicular stomatitis virus (VSV). Besides, another investigation reported that when HBV infection, IFN-γ, and IL-2 are elevated significantly in the patient's serum decided that IFN-γ is required for host antiviral immunity against HBV infection, while "IL-4 and IL-10 which are secreted by T helper-2 cells are associated in the humoral immunity Al-Barzinji, 2009, Ahmed andAl-Barzinji, 2011). ORF 6 protein of SARS-CoV suppresses IFN type 1 production via inhibition of IFN-induced JAK-STAT signaling and preventing the nuclear translocation of phosphorylated STAT1 and consequently hide from innate immunity response" (Perlman and Netland, 2009.…”
Section: Type ⅰ Interferonsmentioning
confidence: 99%